Effects of road development, income inequality and economic growth on private vehicles ownership growth - Poi, Alvin Wai Hoong (2022)
This study postulated that the ratio of motorcycle to car ownership (MPC) could provide an indication of the level of traffic mix that help policy makers push for the best strategy according to the per capita gross domestic product (GDP), relative improvements in road mobility over road accessibility (MPA) and income inequality (GINI). Using a panel dataset of 53 countries between 1963 and 2013, three empirical studies using fixed-effects linear regression and Gompertz function were conducted to test the above argument. The first empirical study indicated that a rise in MPA led to increases in MPC at lower per capita GDP but led to decreases in MPC once per capita GDP exceeds USD$3,081. When the income level surpasses USD$44,767, rising MPA led to increases in MPC again. In the presence of MPA effects, MPC was found to be influenced by income inequality in a reverse U-shaped relationship. In the absence of MPA effects, the reverse U-shaped relationship between MPC and per capita GDP was found to exist under high income inequality condition. The second empirical study found that the direct effects of GDP on MPC were found to be positive at low levels of GDP and turned negative at higher levels of GDP. The indirect effects were transmitted through changes in GINI as GDP rises. The overall effects were found to be greater than the direct effects at both the lower and higher ends of GDP but marginal at GDP level of USD$7,436. The third empirical revealed that the rate of CAR was the highest under mid-range MPA and lower GINI conditions. In contrast, the rate of CAR was the lowest under extreme MPA and higher GINI conditions. In conclusion, lower income countries are expected to observe a rapid rise in motorcycle use if high mobility roads dominate the road network which in turn would face a serious road safety issue. As such, these countries should introduce new or enhance existing regulations on motorcycling, while looking into the feasibility of building dedicated road infrastructure for motorcycles. On the other hand, higher income countries with narrow income gaps and a balanced mix of high mobility and high accessibility roads would observe rapid increase in car use. These countries are recommended to strategize interventions to handle the rise in traffic demand such as increasing the road capacity or introducing policies to control car use.